Development of culture methods capable of culturing a wide range of predominant species of intestinal bacteria - Hirano, Rika; Nishita, Izumi; Nakai, Riho; Bito, Ayaka; Sasabe, Ryunosuke; Kurihara, Shin (Frontiers in Cellular and Infection Microbiology, 2023)
In recent years, with the development of non-cultivation approaches, it has become evident that intestinal bacteria have a significant impact on human health. However, because one-third of the genes cannot be annotated, it is difficult to elucidate the function of all intestinal bacteria by in silico analysis, and it is necessary to study the intestinal bacteria by culturing them. In addition, various media recommended for each individual bacterium have been used for culturing intestinal bacteria; however, the preparation of each medium is complex. To simultaneously culture many bacteria and compare bacterial phenotypes under the same conditions, a medium capable of culturing a wide range of bacteria is needed. In this study, we developed GAM + blood medium (GB medium), which consists of Gifu anaerobic medium containing 5% (v/v) horse blood; it is easy to prepare and it allowed the successful cultivation of 85% of the available predominant species in the human intestinal microbiota.